EVALUATION OF FOUR PROMISING BREAD WHEAT GENOTYPES TO DIFFERENT PHOSPHORUS LEVELS FOR YIELD AND ITS COMPONENTS - Mohammed Al-Falahy; Khalid Dawood; Dilsher Al Mahmada; Shleer Ahmad (Mesopotamia Journal of Agriculture)
The study was done during winter season 2020-2021 at field of College of Agricultural Engineering Sciences, Duhok University, to evaluate the influence of different phosphorus fertilizer P2O5 rate (0, 60, 90, 120kg ha-1 on yield and yield components of four promising bread wheat Bura, Jehan-99, Apst-35 and Apst-26. The experiment was Laid out in factorial experiments using randomize complete block design with three replications. Significant difference in plant height, flag leaf area (cm), spike length(cm), No. seed spike, weight of seed per spike, 1000-seed weight and total yield were observed by the application of different phosphorus fertilizer 120kg ha-1. However, only days to 75% flowering was not significant affected by different rate of phosphorus fertilizer. Also the results exhibited that the Apast-35 was significant in plant height (104.91cm), flag leaf area (40 cm2), spike length (15.4cm), No. seed per spike (37), seed weight of spike (1.48g), 1000-seed weight (41.09g) and total yield 3.66 (t.ha-1). The simple correlation exhibited positive and significant between yield and plant height (0.89), leaf area (0.85), 1000-seed weight (0.76), No. seed per spike (0.87) and weight of seed spike (0.92), this main these traits were intributed to increase the yield under rate 120kg ha-1of phosphorus P2O5.